Detection of Secret Writing by using Various Methods - A Review - Shivanjali S. Ramugade,; Manjushree S. Bagul, (International Journal of Scientific Research in Science and Technology, 2024)
In recent times the secret writing is obtained as key evidence from crime scenes. This plays vital role in solving the crime. Secret writing detection by various methods is easy methods for visualization the invisible messages. numerous techniques have been documented in the literature for revealing secret messages by using various methods. In the present review paper, physical and chemical methods are used for secret writing detection. Secret inks like biological fluids, vegetable juices, fruits juices etc. are use. secret writing using different biological, vegetable, and chemical fluids involves using substances like lemon juice, onion juice, or invisible ink. Heat treatment can reveal hidden messages written with certain substances, while iodine fuming is effective for detecting invisible inks, causing them to become visible.
Keywords: Invisible Inks; Secret Writing; Physical Methods; Chemical Methods; Biological Fluids; Evidence; Chemical Fluids